2013
DOI: 10.1099/ijs.0.053686-0
|View full text |Cite
|
Sign up to set email alerts
|

Sympodiomycopsis yantaiensis sp. nov., a basidiomycetous yeast isolated from insect frass

Abstract: Two strains (NYNU 121010 T and NYNU 121032) of a novel basidiomycetous yeast species belonging to the genus Sympodiomycopsis were isolated from insect frass collected from trunks of a pagoda tree (Sophora japonica L.) in Yantai, Shandong province, east China. The sequence analyses of the D1/D2 domain of the large subunit (LSU) rRNA gene and the internal transcribed spacer (ITS) region indicated that the closest relatives were Sympodiomycopsis kandeliae FIRDI 007 T , Sympodiomycopsis paphiopedili CBS 7429 T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…In a study of yeasts from wood-boring insects, we isolated a large number of yeasts mainly from the digestive tract of beetles as well as from related substrates, including rotted wood, frass and galleries [13], [14]. The majority of the yeast belonged to several major clades in the Saccharomycotina; some of these species have been identified as novel species in earlier papers [13][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of yeasts from wood-boring insects, we isolated a large number of yeasts mainly from the digestive tract of beetles as well as from related substrates, including rotted wood, frass and galleries [13], [14]. The majority of the yeast belonged to several major clades in the Saccharomycotina; some of these species have been identified as novel species in earlier papers [13][16].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the yeast belonged to several major clades in the Saccharomycotina; some of these species have been identified as novel species in earlier papers [13][16]. Amongst the insect associates, we focused on four strains of a sexual ascomycetous yeasts from the frass of beetle larvae in China.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Q. cyanescens (de Beer et al, 2006) and Q. coyrecup (Paap et al, 2008) have been also been described as plant pathogens. The genus Sympodiomycopsis was proposed by Sugiyama et al (1991) and, at the time of writing, includes three described species: S. paphiopedili (Sugiyama et al, 1991), S. kandeliae (Wei et al, 2011) and S. yantaiensis (Chen et al, 2013). The genus Jaminaea comprises J. angkorensis (Sipiczki & Kajdacsi, 2009) and J. lanaiensis (Wei et al, 2011).…”
mentioning
confidence: 99%
“…The genus Sympodiomycopsis, that is sister to Jaminaea, appears to be associated with flowers (Sugiyama et al, 1991;Wei et al, 2011) and insects. The recent description of S. yantaiensis (Chen et al, 2013) showed that the presence of these yeasts in insect frass is probably due to the feeding activities of these insects on flowers. It has been reported that several insects (e.g.…”
mentioning
confidence: 99%
“…The majority of the yeasts belonged to several major clades in the subphylum Saccharomycotina; some of these species have been identified as novel species in earlier papers (Hui et al, 2012(Hui et al, , 2013a(Hui et al, , 2013bChen et al, 2013). Amongst the insect associates, we focused on two strains of an asexual ascomycetous yeast species from the gut of the rhinoceros beetle Allomyrina dichotoma in China.…”
mentioning
confidence: 99%